2019 14th IEEE International Conference on Automatic Face &Amp; Gesture Recognition (FG 2019) 2019
DOI: 10.1109/fg.2019.8756623
|View full text |Cite
|
Sign up to set email alerts
|

AFAR: A Deep Learning Based Tool for Automated Facial Affect Recognition

Abstract: I. MOTIVATIONAutomated facial affect recognition is crucial to multiple domains (e.g., health, education, entertainment). Commercial tools are available but costly and of unknown validity. Opensource ones [1] lack user-friendly GUI for use by nonprogrammers. For both types, evidence of domain transfer and options for retraining for use in new domains typically are lacking.Deep approaches have two key advantages. They typically outperform shallow ones for facial affect recognition [2], [3], [4]. And pre-trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Because manual FACS coding has the disadvantage of being time consuming, automatic detection of FACS AUs has been an active area of research [ 5 ]. Automated facial AU detection systems are available as both commercial tools (e.g., Affectiva, FaceReader) and open-source tools (e.g., OpenFace, [ 6 , 7 ] and Automated Facial Affect Recognition (AFAR) [ 8 , 9 ]). One study found that OpenFace and AFAR generally performed similarly, but average results were slightly better for AFAR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because manual FACS coding has the disadvantage of being time consuming, automatic detection of FACS AUs has been an active area of research [ 5 ]. Automated facial AU detection systems are available as both commercial tools (e.g., Affectiva, FaceReader) and open-source tools (e.g., OpenFace, [ 6 , 7 ] and Automated Facial Affect Recognition (AFAR) [ 8 , 9 ]). One study found that OpenFace and AFAR generally performed similarly, but average results were slightly better for AFAR [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, there has been no systematic comparison of AU detection accuracy among systems. FaceReader is a commercial software designed to analyze facial expressions, whereas OpenFace [ 6 , 7 ] is the dominant shareware automatic facial computing system for many applied situations [ 17 , 18 ], and AFAR is an open-source, state-of-the-art, algorithm-based user-friendly tool for automated AU detection [ 8 , 9 ]. Although comparisons of the performance of these systems are interesting for newcomers and important in terms of system selection, to our best knowledge, no studies have compared these three tools as of yet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mirth response is quantified as the intensity summation of two facial actions units (AU) as defined by the Facial Action Coding System [7]: AU6 (cheek raiser) and AU12 (lip corner puller), which together make the Duchenne smile that represents and signals positive emotion [2,3,9,11]. We acquired the intensity of these 2 AUs using Automatic Facial Affect Recognition (AFAR) [14], a powerful toolkit for assessing severity of negative and positive affect [6,12,13]. We explored its effectiveness to objectively measure mirth response (positive affect) to DBS adjustments.…”
Section: Introductionmentioning
confidence: 99%